PENELITIAN KONSEPTUAL: PENINGKATAN KUALITAS STRATEGIS MELALUI PENGGUNAAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENINGKATKAN KINERJA PEMERINTAH DAERAH - Tatiek Nurhayatie; Muhammad Junaidi; zulkifli zulkifli (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
The quality of planning and synchronization in implementation can be seen from the large number of community participation in the development process. So that public participation in the 4.0 industrial revolution can be realized through the use of technology. The concept offered by this research is the role of Strategic Quality in improving the performance of local government, which places ICT as a moderating variable.